Fabrication of Asymmetric Supercapacitors Based on Coordination Polymer Derived Nanoporous Materials. (20th November 2015) - Salunkhe, Rahul R.; Zakaria, Mohamed B.; Kamachi, Yuichiro; M. Alshehri, Saad; Ahamad, Tansir; Torad, Nagy L.; Dou, Shi Xue; Kim, Jung Ho; Yamauchi, Yusuke
Graphical abstract: Abstract: Considerable efforts have been devoted to the synthesis and characterization of novel nanoporous materials because of their versatile applications, such as gas storage, catalysis, and energy storage applications. Controllable synthesis of coordination polymers (CPs) with two- and three-dimensional architectures has given impetus to the development of nanomaterials with many exciting properties and applications. Here, we focus on CP-derived nanoporous materials and study their electrochemical performance as electrode materials in supercapacitors. Nanoporous carbon is prepared by simple carbonization of zinc-containing zeolitic imidazolate framework (ZIF-8). On the other hand, nanoporous nickel oxide (NiO) is prepared by thermal treatment of cyano-bridged CPs. By using the above two electrodes, we fabricate a novel asymmetric supercapacitor. These CP-derived nanoporous materials exhibit excellent electrochemical performance with high specific energy and specific power, and excellent cycling stability.